Edukasi Personal Review dalam Meningkatkan Ideal Diri dan Aktualisasi Diri Anak Sekolah Menyongsong Indonesia Emas di SMA Negeri 1 Barru - Hastuti, Hastuti; Erika, Kadek Ayu; Fitriani, Nurlaila; Ismail, Nur Syamsu; Hasibia, Nur Hikmawaty (Universitas Baiturrahim, 2026)
Adolescence is a critical period in identity formation, yet it is often marked by an imbalance between the ideal self and self-actualization, which can affect self-confidence and learning motivation. Personal Review training is a reflective approach designed to help adolescents understand their potential, align their ideal self, and enhance self-actualization. This community engagement program was conducted at SMA Negeri 1 Barru on June 19, 2025, involving 50 students from grades X and XI aged 15–18 years. The implementation methods included coordination with the school, development of questionnaires, interactive education sessions, and evaluation through pre-test and post-test. The results showed a significant improvement in students’ knowledge after education, with the proportion of students in the good knowledge category increasing from 60% to 86%, while the poor category decreased from 12% to 0%. This program proved effective in fostering reflective awareness, intrinsic motivation, and self-regulation skills among adolescents. These findings highlight that Personal Review can serve as a school-based intervention model to support character development and adolescent capacity building.